Semiotic Analysis of Kokuji Formation - Stanislaus Joshua; Melinda Dirgandini (DBSMB, Vocational College of Universitas Gadjah Mada, 2022)
Han characters (kanji) used in written Japanese come from China, but there are characters created separately in Japan called kokuji. This research aims to investigate the formation of kokuji according to Peirce’s semiotics and rikusho (traditional classification of Chinese characters) by Xu Shen, and one additional proposed Chinese character category—namely, the kaii-keisei class. The method used in this study is library research. Of the 87 data samples taken from Reiman (1983), shoukei characters made 0% of the total amount, shiji 2.3%, kaii 71.3%, kaii-keisei 4.6%, keisei 19.5%, kasha 2.3%, and tenchuu characters 1%. Analysis results show that the formation of kokuji follows the principles of rikusho. From a semiotic point of view, objects represented by kokuji determine their sign-vehicles. Sign-vehicles are kanji or its components with perceived relations to the object. Sign-vehicles are chosen to form a kokuji based on their ability to represent the object.